Mempertahankan dan Mengembangkan Kebudayaan Melalui Tari Nirok Nanggok Bersama Muda-Mudi dan Anak-Anak Di Desa Kembiri: Artikel Jurnal - Busro, Busro; Fuad, Muhammad; Oktariana, Dina (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2025)
This research is intended as motivation for the community in Kembiri Village to carry out and preserve cultural tradition activities in the "Nirok Nanggok" dance at every opportunity or cultural activity both in Kembiri village and in Membalong sub- district and even throughout Indonesia. The implementation method used is to invite the community to learn each dance movement and its meaning, which in this case is aimed at young people and children from Kembiri village. Dance itself is part of culture, especially the Malay community. Dance aims to preserve culture which is national identity. In the dance itself there are several movements which are symbols of several aspects of life. Dance movements themselves have benefits not only for customs and culture but also for health.